Pembangunan Database Mangrove untuk Biodiversity Informatics Biofarmaka IPB - Yeni Herdiyeni; Ervizal Amir Mahmud Zuhud; Rudi Heryanto (Jurnal Ilmu Pertanian Indonesia, 2014)
Mangroves are a source of traditional medicine that can be used as a source of bioactive compounds. With the conversion of mangrove ecosystem into another designation led to the extinction of mangrove ecosystems. Therefore we need a good management of natural resources. In natural resource management, biodiversity information is needed to sustain the species utilization, exploration potential of the species and their biological and ecological monitoring, policy making, and for the development of biotechnology innovation. Research center of IPB Biopharmaca (Institute for Research and Community Services of Bogor Agricultural University) has the mandate to conduct research from upstream to downstream in the medicinal field. This study develops Indonesian mangrove biodiversity database for Biodiversity Informatics. Biodiversity informatics (BI) is the development of computer-based technologies for the management of biodiversity information. BI can be used to improve the knowledge management (knowledge management), exploration, analysis, synthesis, and interpretation of data ranging from the level of genomic biodiversity, species level to the ecosystem level. From the results of this study are expected data, information and knowledge of natural wealth mangroves can be managed properly so that the preservation of natural resources can be properly maintained and can be used in particular to the field of medicinal studies.